Project-Based Learning in Music Education: A Scopus-Based Bibliometric Review of Research Trends and Intellectual Structure - Gemalia Rahmawati; Bambang Abduljabar; Rama Wijaya Abdul Rozak (Jurnal Paedagogy, 2026)
This study examines the implementation of Project-Based Learning (PjBL) in music education through a bibliometric analysis of Scopus-indexed publications from 2016 to 2025. A total of 479 relevant articles retrieved from the Scopus database were analyzed using VOSviewer to identify research trends, thematic clusters, and the intellectual structure of the field. The analysis focused on keyword co-occurrence, thematic clustering, and publication trends. The results reveal six major thematic clusters: (1) pedagogy and instructional strategies, (2) educational innovation and technology integration, (3) music, creativity, and collaboration, (4) interdisciplinary learning and 21st-century skills, (5) learning evaluation and outcomes, and (6) artificial intelligence and future-oriented music education. Publication trends indicate a substantial increase in research output, particularly after 2022, which coincides with the post-COVID-19 period and the accelerated adoption of digital learning technologies. Overall, this study provides a comprehensive mapping of PjBL research in music education, highlighting both established and emerging research themes and offering valuable implications for curriculum development and future research directions.